MENINGKATKAN KEMAMPUAN METAKOGNITIF DAN AKTIVITAS BELAJAR MELALUI PENERAPAN MODEL PEMBELAJARAN TALKING STICK DI SMPN 1 BALEREJO TAHUN PELAJARAN 2014/2015 - Mia Zhendy Agustina; Marheny Lukitasari (UNIVERSITAS PGRI MADIUN, 2015)
The study aims to determine the improvement of metacognitive skills and learning activities of students through a learning model talking stick. Classroom action research is done in SMPN 1 Balerejo. Data collection techniques metacognitive skills and learning activities using observation sheet . Results of the first cycle study metacognitive skills 44,22. Results of the first cycle of study learning activities 40,3. Results of the second cycle study metacognitive skills 84,74. Results of second cycle studies 82,62. Conclusion there is an increase in metacognitive skills and learning activities of students through the application of learning models talking stick on the subject matter density of population on the environment SMPN1 Balerejo academic year 2014/2015 .